Pengenalan dan Penanganan Masalah Peserta Didik dl RA Bina Hasanah Pangandaran - Dede Mulyana; Galang Pratama; Hilmy Farhani Ali; Mela Rahayu; Neng Ulfa Masyripah; Yustika Ratna Sari (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
The purpose of this study is to describe how the form of recognition and problem solving of students at RA Bina Hasanah Pangandaran. This study uses a descriptive research method with a quantitative approach. The research subjects consisted of one class of students totaling 32 people. Data collection was carried out using problem solving skills test questions in the form of descriptions, and semi-structured interviews with subject teachers and several other students as additional information to support research results. The results showed that the four indicators of problem solving skills were in the good categcny. The percentage offormulating problems is 66.80%; developing a temporcny answer (hypothesis) of 75.39%; planning a solution of 76.95%; and re-checking/concluding 73.83%. Overall, the problem solving skills of RA Bina Hasanah students are in the good categcny with an average of 73.24.